2008
DOI: 10.1261/rna.1318509
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and thermodynamic analysis of the role of start codon/anticodon base pairing during eukaryotic translation initiation

Abstract: Start codon recognition is a crucial event in the initiation of protein synthesis. To gain insight into the mechanism of start codon recognition in eukaryotes, we used a yeast reconstituted initiation system to isolate the step of Met-tRNA i d eIF2 d GTP ternary complex (TC) binding to the 40S subunit. We examined the kinetics and thermodynamics of this step in the presence of base changes in the mRNA start codon and initiator methionyl tRNA anticodon, in order to investigate the effects of base pairing and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
151
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(182 citation statements)
references
References 41 publications
30
151
1
Order By: Relevance
“…Notably, the AUG uORF of YGR210C had the largest impact on the reporter, whereas NCC uORFs had smaller effects. This is consistent with expectations, given the weaker recruitment of ribosomes to NCC start codons (Kolitz et al 2009). The AUG and NCC uORFs we identified appear to function as both positive and negative regulators.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Notably, the AUG uORF of YGR210C had the largest impact on the reporter, whereas NCC uORFs had smaller effects. This is consistent with expectations, given the weaker recruitment of ribosomes to NCC start codons (Kolitz et al 2009). The AUG and NCC uORFs we identified appear to function as both positive and negative regulators.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, AUG uORFs were more occupied than NCC uORFs (Fig. 4D), consistent with their known higher rates of translation initiation (Kolitz et al 2009). Finally, we found that both AUG and NCC uORFs had higher translation efficiency under two stress conditions (rapamycin and diamide treatment) ( In S. cerevisiae, nearly 45% of uORFs initiate with AUG, compared with ∼15% in S. paradoxus and S. uvarum.…”
Section: Comparison Of Aug and Ncc Uorf Functional Characteristicssupporting
confidence: 81%
See 2 more Smart Citations
“…As the start codon mutations in the mRNA mainly affected the on rate for Met-tRNA i Met binding, and not the off rate, it was proposed that 48S PIC formation is accompanied by a conformational change that locks in Met-tRNA i Met binding. Accordingly, in this closed state, Met-tRNA i Met is stably bound to the 40S subunit and fixed on the translation start codon of the mRNA (Kolitz et al 2009). …”
Section: Aug Selectionmentioning
confidence: 99%